Bioassessing the impact of water quality on the health and parasite composition of Oreochromis Mossambicus at the Phalaborwa Industrial Complex (PIC) and the barrage (Olifants river) in the Limpopo Province,South Africa. - Ramollo, Phetole Peter (My University, 2008)
Three sites at the Phalaborwa Industrial Complex (PIC) and one site at the Phalaborwa Barrage in the Olifants River were selected to illustrate the possible influence of different water quality parameters on the health and parasite composition of the Mozambique tilapia (Oreochromis mossambicus). Ten fish were collected seasonally at each site using gill nets of different mesh sizes. Selected water quality variables were determined at all the sites to establish possible differences in water quality between the sites. Hosts were examined for mobile ectoparasites, weighed and measured. Blood samples were drawn and skin smears were made. Fish were killed, dissected and all external and internal organs were examined as prescribed in the fish health assessment index (HAI). The condition factor was determined for each fish population from the different sites. All parasites were collected, fixed and preserved using standard methods. A parasite index(PI), abundance, prevalence and mean intensity of the parasite infestations were calculated.Results obtained for the system variables (pH, water temperature and dissolved oxygen) indicated that the pH levels and water temperature fell within the target water quality range (TWQR) for aquatic ecosystems, but the dissolved oxygen recorded during most of the surveys were below 5mg O2 l-1 which may adversely affect the functioning and survival of biological communities. The mean turbidity values were high at sites A, C and D (caused by fine particles such as silt, clay and organic matter). The total dissolved solids (TDS) and the electrical conductivity (EC) were very high at sites B and C throughout the study. The total water hardness and salinity were also very high at sites B and C which can be attributed to the mine tailings water as well as the geology of the region. The cations (calcium, magnesium and potassium) and anions (chloride, fluoride and sulphate) were above the TWQR for aquatic ecosystems at all sites. The fluoride and sodium levels were high at sites B and C. All the major ions contributed significantly to increased levels of TDS, salinity and EC at sites B and C. The nitrogen and phosphate levels indicated that there was an influx of nutrients into the four sampling sites at varying degrees, which can have an effect on eutrophication conditions at the sampling sites. Trace and heavy metal concentrations differed significantly between all the sites. Aluminium, iron and manganese levels were within the TWQR for aquatic ecosystems at all sites. Copper, lead and zinc levels were above the TWQR and sometimes above the chronic and acute effect values for aquatic ecosystems throughout the study (except for lead concentrations at site A). Thus, the mining activities do affect the water quality at sites B and C adversely in terms of the dissolved salts, nutrients and trace and heavy metals (with the water at site C more impacted than that of site B). The toxicity of some metals is however, dependant on the pH (if it changes to be more acidic, some metals may become toxic) and water hardness of the specific site. The lowest population HAI values (indicating healthier fish populations) were mostly recorded from sites A and D (the sites with better water quality) and the highest at site C(the site with poorer water quality) for three surveys. The high HAI values at site C can mainly be attributed to liver discoloration and abnormal haematological parameters. The fish condition factor values ranged from 0.92 to 1.2 with the lowest mean value recorded at site A and the highest mean value recorded at site B. But, the condition factors indicated that the fish from all sites were generally in good health. The values attained for the haematological parameters, liver discolorations, fins (due to parasitic infestation),abnormal gills, as well as the type of parasites present in/on the fish, were the most indicative parameters in the HAI. No abnormalities in the kidneys, opercules and spleens of fish were observed at any of the four sampling sites during this study. Results from the HAI thus indicated that the fish population from site C was more affected by the water quality (with a higher HAI) compared to the fish populations from the other sites. Also, dissimilar water quality at the different sites affected the health of fish differently. The results recorded for the HAI of the different fish populations thus substantiate the results obtained from the water analysis, indicating that fish from site C (with the poorest water quality) was more affected by their environment. The parasites recorded from O. mossambicus were all site-specific and seem to be moderately influenced by the water quality of the different sites. Some groups, e.g. monogeneans were more affected by the differences in water quality than other parasitic groups. The following ectoparasites were recorded: Cichlidogyrus sp. from the gills and Lernaea cyprinacea and Argulus japonicus from the skin. Endoparasites included digenean larvae from the skin (“black spot”) and gills, Neutraclinostomum larvae in the branchial region, Diplostomum metacercariae from the eyes and swimbladder,Diplostomum tregenna from the brain, dilepidid cestode larvae from the liver and outer surface of the intestine, Contracaecum larvae from the body cavity and sinus venosus of the heart, adult acanthocephalans from the intestine, and pentastomatid larvae of two genera (Subtriquetra rileyi and Alofia sp.) from the swimbladder. The hypothesis that the number of ectoparasites will be lower in more polluted water and the number of endoparasites will be higher was well supported for O. mossambicus at all sites except at site C during Spring survey. The PI for endoparasites was higher at all the mine sites (except during Spring) but similar results were also obtained at sites A and D (the less impacted sites). However, all sites tested during this study were impacted to a lesser or higher degree and the PI for endoparasites can thus be higher at all sites. Some ectoparasites (i.e. Lernaea cyprinacea) were present in high numbers at the more polluted site (site C), but the abundance of monogeneans (also ectoparasites) was most of the time lower at sites B and C, suggesting that monogeneans have been strongly influenced by the poorer water quality at these sites. The specific water parameter/s that influenced the abundance of certain ectoparasites needs further investigation which would most probably best be tested under controlled laboratory conditions. In conclusion, all sites sampled during this study were contaminated to some degree with sites B and C more impacted than the other two sites. The water quality results thus confirmed the results obtained using the HAI and to a lesser extent, the PI. The water quality differed between the four sites and had dissimilar impacts on the health of O. mossambicus and the prevalence of some parasites at the different sites.
Thesis (M.Sc)--University of Limpopo, 2008.
Keywords: Water quality; Oreochroms Mossambicus; Phalaborwa; 553.7; Water Quality